A document made by Paul Thek and Edwin Klein. : Made in Amsterdam, February 1969. (Amsterdam : Stedelijk Museum Amsterdam, 1969)
Photo-collages of newspaper articles. An important collaborative work was created in 1969 by the American artist Paul Thek (1933-1988) and the Dutch photographer and designed Edwin Klein (1946-) for the Pauk Thek and the Artist's Co-op installations at the Stedelijk Museum, Amsterdam, and the Moderne Museet, Stockholm, May 1969
kunstcatalogus
Keywords: Thek, Paul